Isolation and characterization of cellulose degrading bacteria, bacillus flexus from gobar gas digester - SREEREMYA. S; RAJIV. P (International Journal of Pharma and Bio Sciences, 2017)
The major objective of the research is to isolate the potential bacteria from gobar gas digester and analyze the cellulose degrading ability of bacteria for degrading the category III biomedical waste. The standard techniques such as morphological, microscopic, biochemical characterization and preliminary cellulose screening were carried to assess the morphological and biochemical characteristics of selected bacteria. The result showed Bacillus flexus (I2) is the potential cellulose degrading bacteria availed for the degradation of category III biomedical waste.